The influence of hedonic motivation, price, information, and trust on online purchase intention for Tokopedia consumers in Surabaya - Sutandyo, Elyza; Marciano, Deddy; Indarini (Faculty of Business and Economics, University of Surabaya, 2024)
The Covid-19 pandemic has changed human behavior and habits. The development of technology has had a lot of positive impacts that make it easier for people's lives to shop online to meet the needs of life. Tokopedia is one of the trending online shopping platforms and is most in demand by the people of Surabaya during the Covid-19 pandemic where the highest number of engagements on Facebook and Twitter social media is 146,427. This study aims to determine the effect of hedonic motivation, price, information, and trust on online purchase intention on Tokopedia consumers in Surabaya. The causal research-based research was tested empirically using questionnaire data totaling 150 respondents. This research was analyzed using SEM (Structural Equation Modeling) with SPSS 25 software and AMOS 22 software. The results showed that hedonic motivation, online price, and online trust affect the intention to purchase online, then online price affects hedonic motivation, and access to online information affects online trust. Lastly, access to online information does not affect the intention to purchase online.